Open banking - Jeng, Linda (New York, NY Oxford University Press, 2022)
Consumers are growing more aware of the importance and value of the data they personally generate across industries and domains. Financial services is one such area where the link between one's personal data and its economic value is most clearly established, and consumers are beginning to agitate for and gain a measure of agency over their data. A study of the phenomenon of open banking provides a focused lens on the broader phenomena of data proliferation and data monetization. Thus, open banking and its related legal and economic issues along with policy ideas, such as consumer financial data rights, can serve as an interesting model for the broader policy discussion on general data rights. Open banking is a specific manifestation of the revolution of consumer technology in banking and will dramatically change not only how we bank but also the world of finance and how we interact with it. Since the United Kingdom along with the rest of the European Union adopted rules requiring banks to share customer data to improve competition in the banking sector, a wave of countries from Asia to Africa to the Americas have adopted various forms of their own open banking regimes. Among Basel Committee jurisdictions, at least fifteen jurisdictions have some form of open banking, and this number does not even include the many jurisdictions outside the Basel Committee membership with open banking activities. Although U.S. banks and market participants have been sharing customer-permissioned data for the past twenty years and there has been recent but limited policy discussions, such as the Obama administration's failed Consumer Data Privacy Bill and the Data Aggregation Principles of the Consumer Financial Protection Bureau, open banking is still a little-known concept among consumers and policymakers in the States. This book defines the concept of 'open banking' and explores key legal, policy and economic questions raised by open banking"--
Includes bibliographical references and index.
Keywords: Banks and banking -- Electronic books -- Security measures; Confidential communications -- Banking; Financial services industry -- Security measures